IMMUNOLOGICAL ASPECTS OF SPONTANEOUS BACTERIAL PERITONITIS COMPLICATED IN VIRUS ETIOLOGY LIVER CIRRHOSIS - Mukhammadieva M.I (Western European Studies, 2025)
The article presents clinical and laboratory data of the examined patients. 120 patients were under observation. Main group I included 61 patients suffering from liver cirrhosis of viral etiology with SBP, main group II included 59 patients with liver cirrhosis. As a control, 30 practically healthy people were also examined. In all patients with SBP (Group 1) at the stage of decompensation of liver cirrhosis of viral etiology, the level of PCT was significantly higher by 10 times, amounting to 0.88±0.04, compared with patients with uncomplicated SBP (Group 2), in which is equal to 0.08±0.02 (p=0.05). It was found that the level of CRP in the 1st group was 32.4±8.23 and increased by 3.75 times (p=0.05) compared with the 2nd group
Keywords: liver cirrhosis; spontaneous bacterial peritonitis; procalcitonin